CERVICAL INSUFFICIENCY: CAUSES, PRINCIPLES OF DIAGNOSIS AND TREATMENT - Babadjanova, G.S.; Tilavova , G.Y.; Abdurazakova, M.D. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This article provides an in-depth overview of cervical insufficiency (CI) and the strategies for its treatment. It highlights that cervical structural weakness during pregnancy is one of the main causes of preterm birth and perinatal complications. The article discusses the etiological factors, pathogenesis, diagnostic methods, as well as conservative and surgical treatment approaches for CI. In particular, the scientific basis for the effectiveness of progesterone therapy in reducing the risk of preterm birth is analyzed. Clinical outcomes and advantages of different cerclage techniques (McDonald, Shirodkar, and abdominal cerclage) are also reviewed. The study results confirm the important role of progesterone therapy and cerclage procedures in prolonging pregnancy and improving neonatal outcomes. The article emphasizes the necessity of a comprehensive and individualized approach to the management of CI in modern obstetric practice